2013
DOI: 10.1016/j.jvs.2012.06.117
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive bare stent for prevention of stent graft-induced distal redissection after thoracic endovascular aortic repair for type B aortic dissection

Abstract: The mismatch between the distal diameter of the stent graft and the diameter of the compressed true lumen seems to be the major factor in the occurrence of SIDR. Placement of an RBS, as an adjunctive technique to TEVAR, could reduce the incidence of SIDR. On the basis of early- to midterm observations, RBSs may improve morphological remodeling of the dissected aorta at certain levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 34 publications
1
53
0
2
Order By: Relevance
“…16,17 We would consider using bare stents to prevent rupture induced by the proximal stent-graft only when the true lumen is compressed extensively, as others have recommended. 18,19 Although successful treatment of the distal tear at the CA by the combined use of a bare stent and coils has been reported, 20 we still worry about the dislocation of coils and also the effectiveness against large intimal tears. Thus, we think its application is limited.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 We would consider using bare stents to prevent rupture induced by the proximal stent-graft only when the true lumen is compressed extensively, as others have recommended. 18,19 Although successful treatment of the distal tear at the CA by the combined use of a bare stent and coils has been reported, 20 we still worry about the dislocation of coils and also the effectiveness against large intimal tears. Thus, we think its application is limited.…”
Section: Discussionmentioning
confidence: 99%
“…45,50,51,[109][110][111] Distal SINE typically occurs as a late complication and is associated with aortic expansion. 51 Its incidence varies from 6.3% to 27%.…”
Section: Stent-graft-induced New Entry Tearmentioning
confidence: 99%
“…Restrictive bare stenting as an adjunctive technique to TEVAR has been shown to reduce distal SINE in dissected aortas. 111 Notably, there is ongoing debate on this topic, as it is challenging to accurately identify the stent-graft as a cause of new entry tears. 112 …”
Section: Stent-graft-induced New Entry Tearmentioning
confidence: 99%
“…Our previous study indicated that excessive oversizing was potential risk factor of reintervention . It was conceivable that too big oversizing would affect the vascular remodeling of postoperative aorta, resulting in more adverse events such as retrograde type A dissection, stent graft‐induced new entry and distal redissection . Therefore, the oversizing of stent graft for AAD should be recommended and restricted less than 10%, even nearly zero.…”
Section: Discussionmentioning
confidence: 99%
“…21 It was conceivable that too big oversizing would affect the vascular remodeling of postoperative aorta, resulting in more adverse events such as retrograde type A dissection, 22,23 stent graft-induced new entry and distal redissection. 24,25 Therefore, the oversizing of stent graft for AAD should be recommended and restricted less than 10%, even nearly zero. But the reason why the female patients had more adverse events was still obscure.…”
Section: Discussionmentioning
confidence: 99%